Flouting Maxims in the Inside Out Film (2015); Pragmatics Study - Nastha Cecillia Firdaus; Ervina CM Simatupang (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2024)
The purpose of this research is to delve into the field of pragmatics, which involves understanding how meaning is conveyed by a speaker or writer and interpreted by a listener or reader, with a specific focus on instances of conversational flouting in the movie "Inside Out." The descriptive qualitative approach is used in this research to answer the research questions. The flouting maxims were found in some of the conversations from the Inside Out movie along with the function. The results of this research shows that Flouting the maxim of quality and manner is the most common type that has been observed in the characters, each constituting 30% of the data. Different functions were also identified, and the research indicates that characters in the movie predominantly exhibit maxim flouting driven by a single motive—specifically, the competitive function, which constitutes 40% of all the instances observed. Whereas convivial, collaborative, and conflictive functions are not as frequent as competitive functions.